Influences of Chemical Treatment on Mechanical Properties of Rattan - Mohamad Toni, Nur Muhammad; Hj. Mahzan @ Mohd Zin, Prof. Dr. Shahruddin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The current study explores the mechanical properties of untreated and various chemically treated rattan to find its potential as reinforcement in fabrication of advanced composite materials. The rattan will go through various chemical treatments by using alkali and acrylic acid. The most important limitation of rattan is low material durability. The chemical treatment is done to determine whether alkali or acrylic acid has the higher percentages of their initial strength than all fibers after the specified period of exposure in the various mediums. Rattan is an important forest product only second to timber and bamboo and is extensively used as an excellent natural material for furniture, ropes, decorative items, housing, craft products and many more. The mechanical properties of rattan are the most important and most direct performance indicator to determine cane processing and utilization while the most important factors that influence mechanical properties are species, stem position, density and so on. The density will directly affect the strength, hardness, natural durability and many other performances indicators of mechanical properties.